The Private Governance of Identity on the Silk Road - Goanta, Catalina (Frontiers in Blockchain, 2020)
Long before the creation of blockchain platforms, the rise of personal computing and Internet connectivity brought with it a digital, online dimension of the material world, leading to the socio-technical construct known as ‘digital identity’. After the online discussion boards and emailing lists of the early 90s, individuals started socializing via the Internet more predominantly using social networks. One specific type of platform links this online socializing and transacting to blockchain-based spaces: dark web marketplaces. Identified as second-generation cryptocommunities, dark web marketplaces deployed cryptography for the use of pseudonymous identity, for communication, but also currency. This paper explores two questions in this fascinating space: what was the role of identity on the Silk Road, and what governance lessons can be drawn from this illustration for the purpose of applying them to more recent cybercommunities such as Ethereum? The paper is structured as follows. The first part describes the Silk Road and sketches its essential characteristics. The second part looks at how individuals could become platform users on the Silk Road, by analyzing the contractual relationship between the Silk Road and an individual user based on the rights and obligations enshrined in the Silk Road Terms of Service (ToS). The third part critically reflects on arbitrariness as the main pitfall arising out of the private regulatory framework created by the Silk Road, and contributes to existing narratives surrounding the regulatory nature of code by proposing a code-as-procedure perspective for analyzing this regulatory framework. Part four concludes.